Aerodynamic forces on the roofs of low-, mid- and high-rise buildings subject to transient winds. Issue 143 (August 2015) - Jesson, Michael; Sterling, Mark; Letchford, Chris; Baker, Chris
Abstract: Transient winds, such as thunderstorm downbursts, are the cause of design-load wind speeds in many countries. An understanding of the loading experienced by buildings during a downburst is therefore important to allow well designed and engineered buildings to be constructed. In contrast to boundary layer winds, the maximum wind speed in thunderstorm downbursts occurs as low as z m =30 m above the ground, within the range of heights of man-made structures, suggesting that the wind loading will be dependent on the building eaves height relative to z m . In a novel set of experiments, the University of Birmingham Transient Wind Simulator (a 1 m diameter impinging jet with aperture control) has been used to simulate a downburst striking buildings of different heights, ranging from below to above z m . Two forms of building have been used – a square-plan, flat-roofed structure, and a rectangular, portal-frame – at three angles (0°, 45° and 90°) relative to the radial wind direction. Pressure coefficients have been calculated (using eaves height velocity) over the roofs of these buildings, and are shown to be of greatest magnitude when the roof is above the region of maximum outflow velocity, with the exception of windward edges perpendicular to the flow, when they are generally greatest for the lowest building heights. Highlights: Downburst-type flow, including the primary ring vortex, has successfully been simulated in the laboratory using the University of Birmingham Transient Wind Simulator. Aerodynamic pressure coefficients have been measured over cubic and portal-framed building models at a number of wind angles relative to the building (yaw angles). By varying the height of the model building, the effect of building height relative to the vertical position of maximum downburst outflow velocity has been measured. Pressure coefficients are shown to generally be largest for roof heights slightly above the region of maximum outflow velocity. Building height is shown to affect the formation of delta wing-type vortices for cornering winds, the cause of the greatest local suctions.